2015
DOI: 10.1021/jm5016582
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylated Enfuvirtide: A Long-Lasting Glycopeptide with Potent Anti-HIV Activity

Abstract: Many peptide-based therapeutics have short circulatory half-lives. We report here that the pharmacokinetics of an anti-HIV peptide drug enfuvirtide (ENF) can be dramatically improved by a chemical glycosylation approach. A set of glycosylated ENFs with varying glycosylation sites and glycan structures were synthesized. Among these, a sialic acid-introduced peptide (SL-ENF) demonstrated a 15-fold extended half-life in rats relative to ENF (T1/2: 23.1 vs 1.5 h), and its antiviral potency was comparable to that o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 52 publications
(108 reference statements)
1
41
0
Order By: Relevance
“…Notably, the EC 50 value of PEG2k-ENF (4 nM) was comparable to that of ENF (3 nM). The chemical modification at the C-terminus of ENF has an adverse impact on its antiviral activity [11,12,20], because the lipophilic residues (WNWF) in this region are required for the anchoring of the peptide into the membrane interface where the fusion occurs [28,29]. Our data were therefore in agreement with these earlier findings and revealed that the attachment of PEG2k to the N-terminus of ENF did not lead to a significant decrease in its antiviral efficacy.…”
Section: Antiviral Activity Of Ep Conjugates Against a Laboratory-adasupporting
confidence: 91%
See 4 more Smart Citations
“…Notably, the EC 50 value of PEG2k-ENF (4 nM) was comparable to that of ENF (3 nM). The chemical modification at the C-terminus of ENF has an adverse impact on its antiviral activity [11,12,20], because the lipophilic residues (WNWF) in this region are required for the anchoring of the peptide into the membrane interface where the fusion occurs [28,29]. Our data were therefore in agreement with these earlier findings and revealed that the attachment of PEG2k to the N-terminus of ENF did not lead to a significant decrease in its antiviral efficacy.…”
Section: Antiviral Activity Of Ep Conjugates Against a Laboratory-adasupporting
confidence: 91%
“…Following our established glycosylation strategy [20], we investigated the site-specific addition of PEG to the terminus of ENF using a thiol-maleimide coupling reaction ( Fig. 1).…”
Section: Synthesis and Characterization Of Ep Conjugatesmentioning
confidence: 99%
See 3 more Smart Citations